From compound nouns to case marking: Prolatives in South Saami and Lule Saami - Ylikoski, Jussi (Helmut Buske Verlag, 2015)
Published version available in: Hasselblatt C, Wagner-Nagy B. (Eds.): Finnisch-Ugrische Mitteilungen 39, 2015. ISBN: 978-3-87548-745-9. Helmut Buske Verlag. This article discusses the morphology, syntax and semantics of the previously underdescribed denominal formations in -raejkiem and -raejkien in present-day written South Saami, and their etymological and functional counterpart -rájge in Lule Saami. As the topic has been mostly described in occasional dictionary entries but largely ignored in grammatical descriptions, the present article provides the first grammatical description of formations such as South Saami loedteraejkiem ‘along the track’ and okseraejkien ‘through the door’, and the corresponding luoddarájge and uksarájge in Lule Saami. The detailed morphosyntatic and semantic analysis suggests that -raejkiem/-raejkien and -rájge – originating in the genitive and accusative forms of the nouns for ‘hole, opening’ – have many case-like features that make them look like modern equivalents of the so-called prolative (‘along, through, via’) case reconstructed in the (Pre-)Proto- Saami predecessors of these westernmost Uralic languages. In a wider perspective, the development of the case-like -raejkiem/-raejkien and -rájge prolatives from compound nouns challenges received views about diachronic interrelations of compounding, derivation and inflection.